Community participation in local economic development within Mopani district municipality. - Tlakula, Ntsako Desiree (My University, 2014)
Abstract Community participation is increasingly recognised as a big component in planning and development initiatives however the contribution of community members is still limited. Community members still do not understand their roles in planning, implementation, decision-making, monitoring and evaluation of Local Economic Development (LED) initiatives. This study reflects on the need for a culture of community participation in LED processes within Mopani District Municipality. It acknowledges that there are unfavourable conditions that obstruct full community participation. Removing the barriers to community participation can lead to improved planning and better allocation of resources. It will help stakeholders to identify their needs, which will strengthen their voice and encourage them to learn, it will also serve as an opportunity to evaluate their actions, leading to improved decision making. Participatory initiatives will increase the likelihood of success for LED initiatives
Keywords: Community development